Channel integration quality, perceived fluency and omnichannel service usage: The moderating roles of internal and external usage experience - Shen, Xiao-Liang; Li, Yang-Jun; Sun, Yongqiang; Wang, Nan (Decision Support Systems, 2018)
Along with the rapid development of in-store technology, multichannel service is being shifted to omnichannel. By integrating different parallel channels, omnichannel service delivers customers an integrated, seamless and consistent cross-channel shopping experience. To better understand this emerging phenomenon, this study intends to explore the potential drivers of omnichannel service usage. Drawing upon Wixom & Todd framework, this study develops a research model by including object-based beliefs (i.e., channel integration quality) and behavioral beliefs (i.e., perceived fluency). In addition, behavior-based traits (i.e., internal and external usage experience) are hypothesized as moderating the effects of behavioral beliefs on usage behavior. Using an online survey of 401 omnichannel users, the findings demonstrate that channel integration quality significantly affects perceived fluency across different channels, which in turn explains 55% of the variance in omnichannel service usage. The results also show that internal usage experience weakens, whereas external usage experience enhances the effect of perceived fluency on omnichannel service usage. Limitations and implications of this study are further discussed. •This study examined omnichannel service usage by focusing on both object-based beliefs and customer behavioral beliefs.•Perceived fluency explained 55% of the variance in omnichannel service usage.•Channel integration quality significantly affected perceived fluency across different channels.•Relationship between fluency and usage was weakened by internal experience, whereas strengthened by external experience.